Peningkatan Kapasitas Pemasaran Online Bagi Usaha Keripik Tempe Dikelurahan Kauman Ponorogo - Seroliana, Afidha Savella; Antikasari, Tiara Widya; Fitrianna, Nurma; Pratama, Versiandhika Yudha (Yayasan Sagita Akademia Maju, 2024)
Many MSMEs (Micro, Small, and Medium Enterprises) have yet to utilise digital marketing, despite its huge potential and benefits. One of theseMSMEs is a tempeh chips small business owner in Kauman Ponorogo Village. Mrs Misi Rahmawati as the business owner was faced with declining sales levels. With this condition, the business owner is faced with having to try to innovate marketing, so not only offline marketing but also online marketing to increase the amount of income from Mrs Misi Rahmawati, the owner of the tempeh chips business. There is a problem that arises, namely that the owner of this tempeh chips business does not have sufficient knowledge and skills in marketing online. This service is carried out by conducting capacity building activities in online marketing in the form of training and mentoring. The purpose of thisservice activity is to provide understanding, knowledge and skills for business owners in online marketing. The results of this activity are obtaining information about the profile of the tempeh chips business, increasing understanding, knowledge and skills, namely the target tempeh chips business owner in conducting online marketing activities and conducting online marketing in business development.